REYNOLDS NUMBER ESTIMATION OF ROTAMETER BASED ON K-EPSILON MODEL - Bahrudin Bahrudin; Hilman Syaeful Alam (Widyariset, 2017)
Measurement of fluid flow with the aid of a floating element (rotameter) is a simple method used to measure the velocity of the fluid with a better degree of accuracy. However, there is still a tendency for turbulence flow around the floating element (annular area) due to narrowing of the flow area and the geometry shape of the floating element that can reduce the level of the rotameter accuracy. Single phase turbulent flow through rotameter was estimated using k-epsilon turbulence model. Detailed study has been performed to investigate the influence of turbulence characteristics from the Reynolds Number ( ) as a benchmark for predicting the level of turbulence. The results showed that at the velocity of 800 l/h the level  is arounds 450, which show that the fluid flow on the rotameter categorized as turbulence